OP0266 Synovial tissue profiling in autoantibody positive at risk individuals reveals gene signatures associated with later development of rheumatoid arthritis. (12th June 2018) - Van Baarsen, L.G; de Hair, M.J.; Semmelink, J.F.; Choi, I.Y.; Gerlag, D.M.; Tak, P.P.
Abstract : Background: Previous work has suggested subtle infiltration of synovial T cells 1 in the absence of overt synovial inflammation 2 in individuals at risk of developing rheumatoid arthritis (RA). Objectives: To study the molecular changes in synovium preceding arthritis development in preclinical RA. Methods: We included sixty-seven individuals who were IgM rheumatoid factor (RF) and/or anti-citrullinated protein antibody (ACPA) positive and without any evidence of arthritis. All individuals underwent mini-arthroscopic synovial biopsy sampling of a knee joint at inclusion and were prospectively followed. First, an explorative genome-wide transcriptional profiling study was performed on synovial biopsies obtained from 13 individuals using Agilent arrays (test cohort). Survival analysis was used to identify transcripts with a significant association with arthritis development. The expression level of differentially expressed genes was validated using quantitative real-time PCR in the total cohort. Immunohistochemistry was used to study gene candidates at protein level in situ . Results: Six of the 13 individuals in the explorative study developed RA after a median follow up time of 20 months (IQR 2–44). The 7 individuals who did not develop RA had a median follow up time of 85 months (IQR 69–86). Using a False Discovery Rate of <5% we found that increased expression of 3151 transcripts correlated with a higher risk of arthritis development, and increased expression of 2437 transcripts correlated with a lower risk. Gene Set Enrichment Analysis revealed that synovial biopsies of individuals who developed RA after follow up display higher expression of genes involved in several immune response-related pathways (e.g. T cell and B cell receptor pathways, cytokine and chemokine signalling and antigen processing and presentation) compared with biopsies of individuals who did not develop RA. In contrast, lower expression was observed for genes involved in e.g. extracellular matrix receptor interaction, Wnt-mediated signal transduction and lipid metabolism. Subsequently, the expression level of a selection of 27 differentially expressed genes was validated by quantitative real-time PCR in 61 RA-risk individuals. Two-way hierarchical cluster analysis classified the individuals into two groups, where those individuals who developed RA (n=16) showed a preference to cluster together in the left arm of the dendogram (Chi2 p=0.03). Immunohistochemistry analyses (n=54) showed an abundant expression of CXCL12 and CXCR4 already in most RA-risk individuals. Synovial biopsies from RA-risk individuals who developed arthritis were more likely to show a positive gp38 staining and lower lipid staining. Conclusions: This study clearly shows molecular changes appearing in synovial tissue before onset of arthritis in the absence of overt synovitis. Preclinical synovial alterations in immune response genes and lipid metabolism were associated with development of arthritis. References: [1] de Hair MJ, et al. Arthritis Rheumatol 2014. [2] van de Sande MG, et al. Ann Rheum Dis2011. Disclosure of Interest: L. Van Baarsen: None declared, M. de Hair: None declared, J. Semmelink: None declared, I. Choi: None declared, D. Gerlag Employee of: GlaxoSmithKline, UK. GlaxoSmithKline was not involved in this study., P. Tak Employee of: GlaxoSmithKline, UK. GlaxoSmithKline was not involved in this study.